2004
DOI: 10.1055/s-2004-817976
|View full text |Cite
|
Sign up to set email alerts
|

Early Postpartum Hyponatremia in a Patient with Transient Sheehan's Syndrome

Abstract: In modern day health care, Sheehan's syndrome is a rare disorder affecting the postpartum period. We present a case of a 33-year-old woman with atonic hemorrhage developing a transient Sheehan's syndrome associated with hyponatremia six days postpartum. Evaluation of cranial computer tomography and magnetic resonance imaging of the pituitary demonstrated normal finding. Immediate replacement therapy using sodium, chloride, hydrocortisone, fludrocortisone and levothyroxine revealed regression of the Sheehan's s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…In our case, the MRI findings were normal on postpartum day 15 (7 days after the seizure). Two studies reported that the MRI scans were normal on postpartum day 6; in addition, another study reported that normal scans were obtained on day 19 [20, 21, 24]. Seven studies reported their early MRI findings [11, 13, 17, 19, 22, 23, 26].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the MRI findings were normal on postpartum day 15 (7 days after the seizure). Two studies reported that the MRI scans were normal on postpartum day 6; in addition, another study reported that normal scans were obtained on day 19 [20, 21, 24]. Seven studies reported their early MRI findings [11, 13, 17, 19, 22, 23, 26].…”
Section: Discussionmentioning
confidence: 99%
“…6 Whilst our patient had Sheehan's syndrome, there was no history of excess water intake, and her fluid balance remained neutral whilst on the unit; thus, her sodium levels are too low to be explained by thirst centre disruption and her presentation was too acute to have been caused by secondary adrenal insufficiency. 7 There are, however, isolated reports of early onset hyponatraemia after Sheehan's syndrome 8 and SIADH has been reported as a potential cause. 9 Postulated mechanisms involve adrenocorticotrophin deficiency and abnormally high vasopressin secretion in response to mild dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…The time at which hyponatremia is diagnosed ranges from 6 days to 33 years after the initial complicated pregnancy (8,11,24). Diagnosis of SS is usually made several years after postpartum bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought to be caused by ischemic necrosis of the pituitary gland, in association with hypovolemia or shock secondary to massive hemorrhage at delivery. Hyponatremia is a rare early presentation of SS, although severe hypopituitarism may start abruptly after delivery in a small percentage of patients, but most patients have mild symptoms and go undiagnosed and untreated for a long time (up to 42 years) after the initial event (4,5,(7)(8)(9)(10)(11)(12)(13). The occurrence of sodium and water disorders associated with SS depends on extent of pituitary damage, time of onset since the initial pituitary insult, and concurrent medical conditions which also play a role in sodium and water balance.…”
Section: Hyponatremia As the Presenting Manifestation Of Sheehan's Symentioning
confidence: 99%